Economic viability of agri-silvi-horticultural system - M, MUTANAL S; V, MOKASHI M; M, GHATANATTI S (The Indian Journal of Agricultural Sciences, 2019)
An experiment was conducted from 2006-2016 to study the economic viability of sapota timber based agroforestry system at University of Agricultural Sciences, Dharwad on medium black soils under rainfed conditions. The experiment consisted of sapota as major fruit tree species and five timber tree species, viz. Pterocarpus marsupium, Tectona grandis, Terminalia paniculata, Lagerstroemia lanceolata and Terminalia alata which were planted in between two sapota trees. Field crops, viz. soybean and safflower were sown ever year in alleys of sapota + timber trees in kharif and rabi seasons respectively. Recommended package of practices were followed for field crops and sapota trees and all the silviculture practices were followed for better growth of the timber trees. Height, diameter, marketable timber were higher in Tectona grandis with sapota and Lagerstroemia lanceolata with sapota as compared to other tree species. Both net returns, B:C ratio and IRR were higher in the field crops + Sapota + Tectona grandis (` 67129/, 3.84, 123% respectively) followed by field crops + sapota + Pterocarpus marsupium (` 64688, 3.74, 120% respectively) as compared to other tree species.